Peripheral T lymphocyte and immunocyte subset dynamics: markers of neoadjuvant therapy outcomes in esophageal squamous cell carcinoma - Nie, Xin; He, Shuya; Nie, Xinming; Li, Changding; Du, Kunyi; He, Wenwu; Li, Zhiyu; Ni, Kunhan; Lu, Simiao; Wang, Chenghao; Wang, Kangning; Miao, Yan; et al. (Frontiers in Immunology, 2023)
In patients with resectable esophageal squamous cell carcinoma (ESCC), neoadjuvant therapy increased the curative resection rate, disease-free survival, and overall survival for patients with resectable ESCC. However, the efficacy of neoadjuvant therapy varies among different patients. We aim to compare the differences in the characteristics of peripheral blood T lymphocyte subsets before and after neoadjuvant therapy in patients with different curative efficacy. Method: This study enrolled 266 ESCC patients who received neoadjuvant therapy and esophagectomy from August 2018 to August 2022. The postoperative pathological results divided patients into the major pathological response (MPR) and non-MPR groups. Compare the differences in peripheral blood T lymphocyte subsets and analyze the trend of changes in T lymphocyte subsets at different phases of treatment. Propensity score matching was used to reduce the influence of potential confounding factors.Results: Prior to the neoadjuvant therapy, particularly before the second cycle, the MPR group exhibited significantly higher ratios of CD4/CD8 (P=0.009) and helper T cells (TH ratio, P=0.030) compared to the non-MPR group. In contrast, the suppressor T cell ratio (TS ratio) was lower (P=0.016) in the MPR group. The difference in peripheral blood lymphocyte subsets between the two groups of patients who underwent neoadjuvant chemoradiotherapy is significant.In peripheral blood, T lymphocyte subsets varied significantly based on the effectiveness of neoadjuvant treatment. Prior to the second cycle of neoadjuvant therapy, a higher CD4/CD8 and TH ratio, coupled with a decreased TS ratio, might suggest enhanced treatment outcomes.